Transformation of Islamic Education Quality through Regional Autonomy in Bone Bolango Regency, Gorontalo Province - Asiah T., Siti (Jurnal Pendidikan Islam, 2017)
The problem of this research is: What is the condition of Islamic education in Bone Bolango regency before and after the regional autonomy? What barriers exist to improve the quality of Islamic education in the district Bone Bolango? How solutions in improving the quality of Islamic education in the district Bone Bolango? This study used descriptive qualitative method. Engineering data was collected through interviews (interview); observation (observation); documentation. While the validity of the data using triangulation techniques. Results showed before the regional expansion, the condition of Islamic education in the district Bone Bolango still minimal, as evidenced by the number and quality of Islamic education institutions such as MI, MTs, and MA is still below standard. This is caused by the current education management authority is not fully assigned to the area. After the regional autonomy, since holding full authority to manage the region, the district Bone Bolango organized Islamic schools is equivalent to public schools. Problems in improving the quality of Islamic education in the district including the Bone Bolango are Infrastructures, Budget Education, and quality and quantity of human resources as well as community participation to education, and also Public Perception of different Institutions. Solutions to improve the quality of Islamic education in the district Bone Bolango include human resource development by rewarding worthy of professional teachers, improving the professionalism of teachers and educators, supervision of learning, providing adequate infrastructure, applying the model to improve the quality of education in Islamic School.